PENERAPAN MODEL GUIDED INQUIRY DENGAN SUMBER BELAJAR LINGKUNGAN DALAM PENINGKATAN PEMBELAJARAN IPA SISWA KELAS IV SDN 1 SIKAYU TAHUN 2015/2016 - WINDARWATI, WIDI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract. The Application of Guided Inquiry Model Using Environmental Learning Resources in Improving Natural Science Learning for the Fourth Grade Students of SD Negeri Sikayu in the Academic Year of 2015/2016. The objectives of this research are to improve natural science learning through the application of Guided Inquiry using environmental learning resources for the fourth grade students of SD Negeri 1 Sikayu in the academic year of 2015/2016, and (3) to describe problems and solutions. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles in two meetings. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 30 students (16 boys and 14 girls). The conclusion of the application of Guided Inquiry using environmental learning resources through appropriate stages can improve natural science learning about natural resource for the fourth grade students of elementary school. Keywords: Guided Inquiry, environmental learning resources, learning, natural science Abstrak. Penerapan Model Guided Inquiry dengan Sumber Belajar Lingkungan dalam Peningkatan Pembelajaran IPA Siswa Kelas IV SDN I Sikayu Tahun 2015/2016. Tujuan penelitian ini adalah untuk meningkatan pembelajaran IPA tentang sumber daya alam pada siswa kelas IV SD Negeri 1 Sikayu, dan mendeskripsikan kendala dan solusinya. Penelitian ini merupakan penelitian tindakan kelas (PTK) kolaborasi. Penelitian dilaksanakan dalam tiga siklus dengan tiap siklus terdiri dari perencanaan, tindakan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IV SD Negeri 1 Sikayu yang berjumlah 30 siswa terdiri dari 16 siswa laki-laki dan 14 siswa perempuan. Hasil penelitian ini menunjukkan bahwa penerapan model Guided Inquiry dengan sumber belajar lingkungan yang dilaksanakan sesuai langkah yang tepat dapat meningkatkan pembelajaran IPA tentang sumber daya alam pada siswa kelas IV SD. Kata kunci: Guided Inquiry, sumber belajar lingkungan, pembelajaran , IPA